METHODOLOGY OF ORGANIZING AND CONDUCTING PEDAGOGICAL EXPERIMENTAL STUDIES - Mamazhanov Rakhmatilla Yakubjanovich (Web of Journals Publishing, 2025)
The article highlights the methodology of organizing and conducting pedagogical experimental studies. It explains the stages of forming experimental and control groups, developing methodological materials, organizing experimental activities, selecting diagnostic tools, and analyzing results on a scientific basis.
Keywords: Pedagogical experiment, trial studies, methodology, control group, experiment, educational effectiveness.